(untitled) (UNED Research Journal, 2017)
Diarrhoea is the second leading cause of infectious morbidity and mortality in children under five years of age. This study aimed at identifying the most common parasites and potential risk factors for diarrhoea among children 0-5 years attending Abia State Specialist hospital and Federal Medical Centre, Umuahia, in south eastern Nigeria. We used 400 faecal samples from children with diarrhoea –and 200 without– in combination with hospital-based case control and a questionnaire Stool samples were processed with direct normal saline and formal-ether sedimentation method for parasitological studies. More males than females were infected in nearly all age groups in both diarrhoeal and control groups (X2=23.04, df=1, P<0.05: X2=11.52, df=1, P<0.05 respectively). Amachara had more infections (X2=0.15, df=1, P< 0.05). January had the highest rate of infection (22.5%). Main clinical features were watery depositions over 3 times a day, diarrhoea lasting for days, fever, vomiting, and dehydration. Mothers learned about the problem through health workers, television and in medical centers. Risk correlated with mother’s education, occupation, latrine type, waste water disposal, hand washing, kitchen cleaning; sources and storage of water; and bottle milk (P< 0.05).Ignorance greatly contributed to the spread of parasitic disease in the area: the government should improve education and other strategies to alleviate the spread of the disease..